Transient load concentration factor due to a sudden break of fibers in the viscoelastic PMC under tensile loading. (15th June 2016) - Reza, Arash; Shishesaz, Mohammad
Abstract: This study aims to investigate the effect of viscoelasticity of polymeric matrix of composite materials on the transient stress concentration due to a sudden break in its fibers. The fibers were modeled as a linear elastic, and the matrix was modeled as a linear viscoelastic material. A generalized Voigt–Kelvin solid model was employed to model the viscoelastic behavior of matrix. In this study, finite difference method and an innovative semi-analytical method were used. The governing integro-differential equations have been derived by shear-lag theory and have been solved by initial and boundary conditions before and after break occurrence. The governing equations contain an integral term attributing to the viscoelastic properties of the matrix. The same analysis was conducted for the laminae and laminates with fibers arranged in square and hexagonal arrays. Results obtained from the two methods show a relatively good match. The results show that assuming viscoelastic properties decreases the peak of stress concentration factor and increases the steady stress concentration factor. Finally, the effects of size and location of break in the fibers for lamina and laminated composite were investigated.